Trade-Off Theory versus Pecking Order Theory: capital structure decisions in a peripheral region of Portugal - Serrasqueiro, Zélia; Caetano, Ana (Journal of Business Economics and Management, 2014)
This paper seeks to analyse whether the capital structure decisions of Small and Medium-Sized Enterprises (SMEs) are closer to the assumptions of Trade-Off Theory or to those of Pecking Order Theory. We use a sample of SMEs located in the interior region of Portugal, using the LSDVC dynamic estimator as method of estimation, the empirical evidence obtained allows us to conclude that the most profitable and oldest SMEs resort less to debt, which corroborates the forecasts of Pecking Order Theory. SMEs, with greater size, resort more to debt, corroborating the forecasts of Trade-Off Theory and Pecking Order Theory. In addition, SMEs adjust noticeably their current level of debt towards the optimal debt ratio, which corroborates what is forecast by Trade-Off Theory. Therefore, this paper enhances that Trade-Off and Pecking Order Theories are not mutually exclusive in explaining the capital structure decisions of SMEs. The results suggest that younger and smaller SMEs should be object of public financing support, when the internal financing is clearly insufficient to fund those firms’ activities.